2015
DOI: 10.3892/mmr.2015.3585
|View full text |Cite
|
Sign up to set email alerts
|

Propofol post-conditioning protects the blood brain barrier by decreasing matrix metalloproteinase-9 and aquaporin-4 expression and improves the neurobehavioral outcome in a rat model of focal cerebral ischemia-reperfusion injury

Abstract: Abstract. Propofol, an intravenous anesthetic, inhibits neuronal apoptosis induced by ischemic stroke, protects the brain from ischemia/reperfusion injury and improves neuronal function. However, whether propofol is able to protect the blood brain barrier (BBB) and the underlying mechanisms have remained to be elucidated. In the present study, a rat model of cerebral ischemia/reperfusion was established, using a thread embolism to achieve middle cerebral artery occlusion. Rats were treated with propofol (propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
4
21
0
1
Order By: Relevance
“…Although GA did not impact the most severe hemorrhage subtypes (sICH and PH), these findings provide signals about its protective effect against hemorrhage that warrant further exploration. While no definitive explanation regarding the relationship between GA and ICH can be drawn from our data, there are several theoretical possibilities: (1) less patient motion in the setting of GA with more precise intracranial navigation and lower chance of microvascular avulsion; (2) protective effect of anesthetic medications against cerebral ischemic reperfusion injury12–15; (3) reduced pain and agitation with lower chance of blood pressure surges and uncontrolled hypertension, which is an independent risk of HT 16. In addition, hypotension that frequently occurs with GA during thrombectomy may also protect the ischemic tissue against HT after reperfusion.…”
Section: Discussionmentioning
confidence: 88%
“…Although GA did not impact the most severe hemorrhage subtypes (sICH and PH), these findings provide signals about its protective effect against hemorrhage that warrant further exploration. While no definitive explanation regarding the relationship between GA and ICH can be drawn from our data, there are several theoretical possibilities: (1) less patient motion in the setting of GA with more precise intracranial navigation and lower chance of microvascular avulsion; (2) protective effect of anesthetic medications against cerebral ischemic reperfusion injury12–15; (3) reduced pain and agitation with lower chance of blood pressure surges and uncontrolled hypertension, which is an independent risk of HT 16. In addition, hypotension that frequently occurs with GA during thrombectomy may also protect the ischemic tissue against HT after reperfusion.…”
Section: Discussionmentioning
confidence: 88%
“…Some of stresses known to induce increases in the JNK1/2 phosphorylation status include, exposure to reactive oxygen species (ROS), mechanical shear stress and a hyperosmolar challenge 13, 44, 45 . In vitro and in vivo results showed that LPS decreases AQP5 expression through the p-JNK/NF-κβ signaling pathway 46, 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of MMP-9 affects the integrity of the vascular basal membrane, thus resulting in severe blood–brain barrier damage and the entry of plasma proteins and a variety of substances and metabolites into the brain, which causes vasogenic edema and the entry of inflammatory cells into brain tissues [79]. Reductions in the expression of MMP-9 have been shown to significantly improve cerebral ischemia–reperfusion injuries in rats [10]. However, it is unclear if serum ADP and MMP-9 are involved in the pathophysiological processes underlying POCD.…”
Section: Introductionmentioning
confidence: 99%